Karakteristik Daging dengan Penambahan NaCl pada Berbagai Waktu Aging Post Mortem - Hatta, Wahniyathi; Hermanianto, Joko; Maheswari, Rarah RA (Fakultas Peternakan Universitas Jambi, 2006)
It is important to maintain meat characteristics after slaughtering because its relationship with preferences and economics values of meat and meat product. Salt addition is an alternative. The aim of this research was to observe influence of salt addition on meat characteristics during the first 7 day of post mortem aging. Meat sample was divided into three groups of salt added treatments : 1) without salt addition, 2) salt added at one day prior to aging, and 3) salt added every day along aging period. The results showed that salt added at the zero day was to increase pH, solubility of salt-soluble protein, and water holding capasity (WHC) to a higher level compared to the other two treatments. Although salt addition may increased the meat characteristics, decreasing these characteristics could not be avoided when the meat stored for 7 day post mortem aging.